Grain yield and protein content in F6 lines of Triticum aestivum obtained by Single Seed Descent - Cerfonteyn, Henk (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.Agric.) -- University of Stellenbosch, 1985.